RESPONSIBILITY OF GRADUATES BACHELORS OF THE SPHERE OF SERVICE, TOURISM AND HOSPITALITY: SOCIAL AND PSYCHOLOGICAL ASPECT - V. Timofeycheva (Вестник университета)
In the article the theoretical review of the modern social and psychological researches devoted to studying of responsibility as professionally important quality of the graduate bachelor of the sphere of service, tourism and hospitality is offered and also different views of scientists on feature of vocational training of bachelors of the sphere of service, tourism and hospitality, in the light of formation of their psychological readiness for implementation of professional activity are considered.